Організація розрахунку стійкості складної ЕЕС з урахуванням мікропроцесорного регулятора потужності турбін АЕС - Авраменко, В.М.; Юнєєва, Н.Т.; Коровко, А.М. (Технічна електродинаміка, 2012)
Improved program complex calculating the stability of complex EPS, which includes a block of modeling the MP power regulator of NPP turbines, ensuring correct account of such regulator and emergency control settings to improve the dynamic stability of nuclear power plants. Calculations of the dynamical stability of the EPS under regulatory perturbations are graphs showing the corresponding results.